Proses Kreatif Pengarang Ehon Kondou Eri pada karya Raion To Usagi - Sulastri (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2025)
This research examines children's picture books as literary works produced through a series of creative processes. The purpose of this study is to reveal the creative process that Kondou went through as an author and illustrator of a children's picture book entitled Raion to Usagi. A qualitative descriptive approach is used in this research to find out Kondou's creative process in the process of creating Raion to Usagi. Data is collected using the interview method and will be analyzed based on the five stages of the creative process proposed by Isnéndés. Based on the analysis results, it was found that Kondou has gone through five stages of the creative process including: (1) the approach stage, influenced by her favorite animal, the rabbit. This stage is also influenced by nine mental factors, namely spontaneity, intuition, contemplation, intelligence, personality, experience, emotion, concept of art and imagination; (2) the discovery stage includes how Kondou turns ideas into picture books and the essence of the story to be conveyed; (3) the composing stage to create Raion to Usagi, which takes one year; (4) the expression stage which relies on the expressions of the characters; and (5) the communication stage, namely selling this book in kindergartens and daycare centers. The results show that Kondou consistently goes through these five stages in creating and communicating Raion to Usagi as a work of visual literature for children.